2016
DOI: 10.1097/mpa.0000000000000591
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Computerized Tomography and Magnetic Resonance Imaging of the Pancreas Predicts Pancreatic Mass and Functional Outcomes After Total Pancreatectomy and Islet Autotransplant

Abstract: Objectives About two-thirds of patients will remain on insulin therapy after total pancreatectomy with islet autotransplant (TPIAT) for chronic pancreatitis. We investigated the relationship between measured pancreas volume on computerized tomography (CT) or magnetic resonance imaging (MRI), and features of chronic pancreatiits on imaging, with subsequent islet isolation and diabetes outcomes. Methods CT or MRI was reviewed for pancreas volume (Vitrea software), and presence or absence of calcifications, atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Samples were labeled such that identical numbers denote samples from the same patient, and distinct tissue regions were denoted by letters. Severity of pancreatic fibrosis was assessed using a standardized approach by the islet laboratory facility on a scale of 0–10, as previously described ( 35 , 39 ). In brief, resected pancreases were assessed for firmness and texture and assigned an initial score of 1 (minimal change), 3 (mildly fibrotic), 5 (moderately fibrotic), 7 (very fibrotic), or 9 (severely fibrotic) to estimate the extent of fibrosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were labeled such that identical numbers denote samples from the same patient, and distinct tissue regions were denoted by letters. Severity of pancreatic fibrosis was assessed using a standardized approach by the islet laboratory facility on a scale of 0–10, as previously described ( 35 , 39 ). In brief, resected pancreases were assessed for firmness and texture and assigned an initial score of 1 (minimal change), 3 (mildly fibrotic), 5 (moderately fibrotic), 7 (very fibrotic), or 9 (severely fibrotic) to estimate the extent of fibrosis.…”
Section: Methodsmentioning
confidence: 99%
“…Pain is frequently the most debilitating symptom and is the primary indicator for surgical intervention ( 32 ), although it is poorly predicted by imaging analyses ( 33 ). Severe fibrosis is a feature of advanced disease and is correlated with progressive pancreatic dysfunction ( 34 , 35 ). Calcification, resulting from recurrent inflammation, is also considered a classical hallmark of severe chronic pancreatitis ( 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…Large series have reported significantly higher islet yields in pediatric patients, possibly related to a decreased number of prior surgical interventions which are independently associated with higher rates of islet graft failure 1 year post-operatively [6]. The etiology of CP is variably predictive, and patients with alcoholism or hereditary pancreatitis may have lower pancreas volumes, increased pancreatic structural changes, lower islet yields, and increased risk of islet graft failure, while those with idiopathic pancreatitis may have lower risks of islet graft failure [6,9,10]. Multiple studies have also demonstrated the relationship between longer disease duration and duration of narcotic use with low islet yield and graft failure (Table 2) [6,11].…”
Section: Factors Predicting Outcomesmentioning
confidence: 99%
“…MRI and computerized tomography (CT) scanning can generate 3-dimensional images of the pancreas and accurately calculate the volume of the pancreas, as well as assess for the presence of structural changes including: parenchymal calcifications, atrophy, and dilation of the main pancreatic duct. Islet yield has been understandably correlated with increased pancreatic mass, and mean islet yield has been reported to be decreased by 50% if any structural changes are demonstrated on imaging [9]. Calcifications in particular increase the odds of insulin dependence greatly, with only 15% of those with calcifications being insulin independent 1-year postoperatively [9].…”
Section: Pre-operative Imagingmentioning
confidence: 99%
See 1 more Smart Citation